Vertical transportation of men, material and mineral from ultradeep mining operations - an analysis of options - Muzoriwa, Clarkson Mutungagore (My University, 2000)
Single-stage hoisting from ultra-deep level mining operations is vital for sustainable exploitation of mineral deposits beyond current depths( <3000m). Analysis of options available to hoist men, material, and ore takes the form of industry visits, the study of cases, proposed and new ideas. Operational feasibility is done by the analysis of the methods available. Underground mineral processing is discussed with a view to combining it with other available hoisting methods and taking advantage of likely spin-offs. New materials for ropes, conveyances and pumping accessories, and other options are discussed. Power consumption and consequently unit cost of the same is used extensively in evaluating the possible transportation scenarios. Skip hoisting with a revised factor of safety regulations and new rope materials is still an attractive option so is the concept of hydraulic hoisting of fine material with a centrifugal pump. Rope-less technology is still futuristic for all practical intent
A project report was submitted in partial fulfillment of the requirements for the degree of Master of Science in Engineering to the Faculty of Engineering, University of the Witwatersrand, Johannesburg, 2000
Keywords: Mine haulage; Mine hoisting